Preliminary Study on the Structure of the Atmospheric Surface Layer in Mizuho Plateau, East Antarctica (Special Issue of the Proceedings of the First Symposium on Antarctic Meteorology and Glaciology) - Hiroshi SASAKI (National Institute of Polar Research, 1979)
A preliminary study on the structure of the atmospherlc surface layer in Mlzuho Plateau, East Antarctica was made based on the profiles and fluctuations of wind and air temperature observed at Mizuho Station during the period from June to December 1972 The results are summarized as follows : 1) High frequency of slightly stable conditions and low frequency of unstable conditions were a characteristic feature of stability in the atmospheric surface layer in Mizuho Plateau during the period described above 2) Mean value of roughness length was 0.24 cm and larger by one order than the values at Syowa Station and the South Pole. This may be explained by the presence of high sastrugi produced by erosion of katabatic winds in Mizuho Plateau The profiles of wind speed near the snow surface followed the "log+lmear" law for Richardson numbers less than about 0.1 3)The distributions of the power soectra of wind and temperature fluctuations and those of the cospectra of heat flux were similar to the results reported by many investigators. The cospectral analysis for momentum shows that the momentum with positive sign is transferred within some frequency ranges. It appears that the probability density distributions of the vertical velocity fluctuations in katabatic winds are skew to the region smaller than the mean values 4) Temperature oscillations which seem to be caused by internal wave motions were observed in winter.